Women’s Experiences of Reproductive Coercion: Mental Health Outcomes - Abbaszadeh Hajiabadi, Zeinab; Soltaninezhad, Mahla; Seyadat, Sakineh; Yavari Kermani, Maryam (Psychology of Woman Journal, 2024)
Objective: Reproductive coercion is a form of abuse where one’s reproductive rights and decisions are controlled or manipulated, often leading to significant mental and physical health implications. This study aims to explore the experiences of reproductive coercion among women, focusing on its emotional impact, physical health consequences, and the coping mechanisms employed by the victims. Methods and Materials: Employing a qualitative research design, this study conducted semi-structured interviews with 22 women who have experienced reproductive coercion. The interviews aimed to achieve theoretical saturation and provide in-depth insights into the participants’ experiences. Thematic analysis was utilized to identify key themes and patterns in the data. Findings: The analysis revealed three main themes: the emotional impact, physical health consequences, and coping mechanisms of reproductive coercion. Participants reported significant fear and anxiety, loss of control, depression, isolation, and guilt and shame. Physical health consequences included reproductive health issues and physical injuries. To cope with these challenges, women employed strategies such as seeking help, adaptation, resistance and assertiveness, and self-care and recovery. Conclusion: Reproductive coercion significantly impacts women’s mental and physical health, highlighting the need for targeted interventions and support. This study contributes to the understanding of reproductive coercion’s multifaceted impact, emphasizing the importance of addressing this issue in healthcare and support services to mitigate its effects on affected women.